2024
DOI: 10.3390/min14030297
|View full text |Cite
|
Sign up to set email alerts
|

Genesis of the Dongtangzi Zn-Pb Deposit of the Fengxian–Taibai Ore Cluster in West Qinling, China: Constraints from Rb-Sr and Sm-Nd Geochronology, and In Situ S-Pb Isotopes

Qiaoqing Hu,
Yitian Wang,
Shaocong Chen
et al.

Abstract: The large Dongtangzi Zn-Pb deposit is located in the southwest of the Fengxian–Taibai (abbreviated as Fengtai) ore cluster in the west Qinling orogen. The origin of the deposit is controversial, positing diverse genesis mechanisms such as sedimentary-exhalative (SEDEX), sedimentary-reformed, and epigenetic-hydrothermal types. This study combines systematic ore geology observations with high-precision Rb-Sr and Sm-Nd ages of 211 Ma and in situ S-Pb isotopes to constrain the timing and origin of mineralization. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…Most previous studies suggested that the Pb-Zn mineralization resulted from Devonian sedimentary-exhalative processes. New geochronologic, stable and radiogenic isotopic, and trace element data indicate that the representative Qiandongshan-Dongtangzi Pb-Zn deposit is not the product of sedimentary-exhalative processes, but is rather the product of epigenetic magmatic hydrothermal fluid processes, driven by regional tectono-magmatic activities in the Late Triassic Epoch [4,5].…”
mentioning
confidence: 99%
“…Most previous studies suggested that the Pb-Zn mineralization resulted from Devonian sedimentary-exhalative processes. New geochronologic, stable and radiogenic isotopic, and trace element data indicate that the representative Qiandongshan-Dongtangzi Pb-Zn deposit is not the product of sedimentary-exhalative processes, but is rather the product of epigenetic magmatic hydrothermal fluid processes, driven by regional tectono-magmatic activities in the Late Triassic Epoch [4,5].…”
mentioning
confidence: 99%